2023
DOI: 10.1002/adfm.202300363
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Formation Dynamics and Band‐Like Free Charge‐Carrier Transport in 2D Metal Halide Perovskite Semiconductors

Abstract: Metal halide perovskite (MHP) semiconductors have driven a revolution in optoelectronic technologies over the last decade, in particular for high‐efficiency photovoltaic applications. Low‐dimensional MHPs presenting electronic confinement have promising additional prospects in light emission and quantum technologies. However, the optimisation of such applications requires a comprehensive understanding of the nature of charge carriers and their transport mechanisms. This study employs a combination of ultrafast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 95 publications
3
14
0
Order By: Relevance
“…For excitation at 410 nm, it can be assumed that j ≈ 1 at early times since the excitation energy is well above the excitonic absorption feature and an equilibrium between excitions and free carriers has not yet been established [20]. For (PEA) 2 PbI 4 excited at 410 nm, we find the effective charge-carrier mobility to be 5.8 ± 0.9 cm 2 V −1 s −1 , consistent with other reports in literature [10,20,23]. Similarly, photoexciation at 450 nm yeilds a charge-carrier mobility value of 5.4 ± 0.2 cm 2 V −1 s −1 An effective charge-carrier mobility of 1.9 ± 0.5 cm 2 V −1 s −1 is estimated from the decay traces following resonant exciation to the excitonic states at 514 nm.…”
Section: Optical Pump-terahertz Probe (Optp)supporting
confidence: 88%
See 3 more Smart Citations
“…For excitation at 410 nm, it can be assumed that j ≈ 1 at early times since the excitation energy is well above the excitonic absorption feature and an equilibrium between excitions and free carriers has not yet been established [20]. For (PEA) 2 PbI 4 excited at 410 nm, we find the effective charge-carrier mobility to be 5.8 ± 0.9 cm 2 V −1 s −1 , consistent with other reports in literature [10,20,23]. Similarly, photoexciation at 450 nm yeilds a charge-carrier mobility value of 5.4 ± 0.2 cm 2 V −1 s −1 An effective charge-carrier mobility of 1.9 ± 0.5 cm 2 V −1 s −1 is estimated from the decay traces following resonant exciation to the excitonic states at 514 nm.…”
Section: Optical Pump-terahertz Probe (Optp)supporting
confidence: 88%
“…To confirm that we are only observing free-charge carriers and not excitons, photoconductivity spectra between 0.5-3.5 THz were obtained at excitation wavelengths of 410 and 514 nm (see SI, figure S6). In both cases, the real and imaginary photoconductivity components have a free charge-carrier (Drude-like) response that has been observed in the THz photoconductivity spectra of perovskites including MAPbI 3 and LPKs [23,55,68]. There is also no evidence of a resonance feature, confirming that we are likely probing only a freecarrier response.…”
Section: Optical Pump-terahertz Probe (Optp)supporting
confidence: 69%
See 2 more Smart Citations
“…Combined with the narrowed PL band tails, it could be confirmed that the suppressed interface defect favored the mitigation of energetic disorder near the band edge and shielded the carriers from nonradiative relaxation. 26,27…”
Section: Resultsmentioning
confidence: 99%